Open access to social science journals in Latin America - Babini, Dominique (UNESCO, 2021)
During the 2000s, Latin America has contributed to the development of alternative journal portals intended to improve the visibility of and access to regionally published social science journals. The relatively poor visibility of regional journals and their authors is often due to budgetary constraints for the distribution of printed journals, and their limited presence in international indexes. These are an incentive for the development of open access (OA). Although they do not yet necessarily have a sustainable business model, a number of Latin American journals have chosen to take up the challenge of online OA as a means of dealing with these problems.